Static water quality monitoring system - Liew, Hau Run (2021)
This project discusses about the static water monitoring system using Internet of Things (IoT). As the population in the world increases, the demand for seafood also increases accordingly. Therefore, there is a need to have a low cost, low power consumption and compact water monitoring system that allows aquaculture farmers to evaluate and monitor the quality of the water at all times. The purpose of the water monitoring system is to ensure the quality of the water is kept at an acceptable level so that the aquaculture are not affected. The parameter that will be monitored istemperature of the water. The embedded system used consists of the Arduino platform along with the ThingSpeak cloud server. Arduino Mega is the chosen microcontroller and is used to log data from the temperature sensor, then the data is stored into the SD card and uploaded to the ThingSpeak Cloud server if the connection to data network is established. The Arduino SIM900A GSM GPRS is the communication module used to for data transmission between the Arduino Mega and the ThingSpeak Cloud server. The water parameters are monitored and the data can be shown on the ThingShow mobile application in graphical form. The mobile application can show historical data according to the date and time. The data will be logged at a fixed interval of one hour. The temperature data is collected at two distinct locations where one location is significantly more exposed to sunlight than the other location. Additional sensors can be added in the future to collect more water parameters. The system also consists of a hoist mechanism to lower the sensor into the water when measurement is needed and lift the sensor when the measurement is done. In conclusion, the static water monitoring system can help aquaculture farmers monitor water parameters regularly with less human workers. This will save aquaculture farmers a lot of time and cost. Aquaculture farmers can also find countermeasures to solve the problems that arises before the aquaculture are affected.